Synthesis, Cyclooxygenase Inhibition, Anti‐Inflammatory Evaluation, and Ulcerogenic Liability of New 1, 3, 5‐Triarylpyrazoline Derivatives Possessing a Methanesulfonyl Pharmacophore. Issue 10 (7th September 2016) - Abdellatif, Khaled R. A.; Fadaly, Wael A. A.; Azouz, Amany A.
Abstract : A new series of 1, 3, 5‐triarylpyrazolines13a–l was synthesized and all prepared compounds were evaluated for their in vitro COX‐1/COX‐2 inhibitory activity and in vivo anti‐inflammatory activity. All test compounds were more selective for the COX‐2 isozyme and showed good in vivo anti‐inflammatory activity. Compound13h was the most COX‐2 selective compound (COX‐2 selectivity index (SI) = 10.23) and the most potent anti‐inflammatory derivative (ED50  = 60.1 µmol/kg) in comparison with celecoxib (COX‐2 SI = 9.29 and ED50  = 81.4 µmol/kg). All screened compounds were less ulcerogenic (ulcer indexes (UI) = 0.33–1.33) than aspirin (UI = 2.33) and comparable to celecoxib (UI = 0.33). Abstract : A new series of 1, 3, 5‐triarylpyrazolines were evaluated for their in vitro COX‐1/COX‐2 inhibitory activity and in vivo anti‐inflammatory activity. All new compounds were more selective for the COX‐2 isozyme and showed good in vivo anti‐inflammatory activity. In addition, all screened compounds were less ulcerogenic than acetylsalicylic acid but comparably ulcerogenic to celecoxib.